Zoonosis and reverse zoonosis of SARS-CoV-2 from the perspective of the One Health - Norberg, Antonio Neres; Norberg Blanco Moreira , Paulo Roberto; Mangiavacchi, Bianca Magnelli; Ferreira Filho, Renato Mataveli; Faial, Lígia Cordeiro Matos; Colete, Claudia Caixeta Franco Andrade; Martins, Lívia Mattos; de Sant’Anna, Nadir Francisca; Nunes, Clara dos Reis; Brasil Borges, Thaís Rigueti; Medeiros de Matos, Maria de Lourdes Ferreira; de Campos, Ivy (Seven Editora, 2023)
According to the WHO, as of July 26, 2022, there were 568,773,510 confirmed cases of COVID-19 and 6,381,643 deaths recorded because of this disease worldwide (WHO, 2022). The etiologic agent of COVID-19 is the SARS-CoV-2 coronavirus, an RNA virus of the family Coronaviridae and subfamily Orthocoronavirinae (XAVIER et al., 2020). Humans infected with SARS-CoV-2 have clinical signs such as fever, non-productive cough, shortness of breath, and may progress to pneumonia, acute respiratory syndrome, and kidney failure, although a few other signs, symptoms, and clinical forms may be observed less frequently (SAXENA et al., 2020). The evolution of the infection to severe acute respiratory syndrome can lead to death from COVID-19. These patients have a strong inflammatory response, like that of cytokine release syndrome, and increased migration of neutrophils to lung tissue triggered by inflammatory mediators released by epithelial, endothelial cells of infected tissue and by immune system cells attracted to the site of infection (MANGIAVACCHI et al., 2020; MERAD et al. 2022; BHARDWAJ et al., 2022; LI & LI, 2022). DOI: https://doi.org/10.56238/emerrelcovid19-006